Internet Addiction: Prevalence and Patterns among Professional College Students in Urban Area – A Cross-sectional Study - Aditya Oruganti; Jaya Chandra Muppa; Balakrishna Kolanati; Avinash Kavi (Journal of Public Health and Primary Care)
Background: Internet addiction, characterized by excessive and compulsive online behavior, has become a global issue, particularly among students. India, with its rapidly growing internet population, is witnessing a surge in Internet addiction among youth and, especially professional college students. Objectives: This study aims to assess the prevalence and patterns of Internet addiction among medical and engineering college students in Belagavi, Karnataka. Methodology: A cross-sectional study was conducted among 640 students (320 medical and 320 engineering) using simple random sampling. Data were collected from participants who have used the Internet for at least 6 months via a self-administered questionnaire, including Young’s Internet Addiction Scale, categorizing addiction into normal, mild, moderate, and severe levels. Statistical analysis was performed using SPSS version 25.0. Results: Of the medical students, 58.4% were moderately addicted, 32.5% were mildly addicted, and 6.3% were severely addicted. Among engineering students, 74.4% were moderately addicted, 15.6% were mildly addicted, and 8.4% were severely addicted. Engineering students exhibited significantly higher levels of addiction compared to medical students (P < 0.05), with behavioral differences in compulsive Internet use and emotional responses. Conclusion: The study reveals a high prevalence of Internet addiction among professional college students, with engineering students showing a higher tendency toward problematic use. These findings underscore the need for early intervention and awareness programs to address Internet addiction and its consequences on students’ well-being.